Concordance of Epidermal Growth Factor Receptor Mutation from Tissue Biopsy and Plasma Circulating Tumor DNA in Treatment-Naïve Lung Adenocarcinoma Patients - Soeroso, Noni Novisari; Taufik, Hendra; Tarigan, Setia Putra; Mutiara, Erna (Open access Macedonian journal of medical sciences, 2022)
Background: Prevalence of Epidermal Growth Factor Receptor (EGFR) mutation in ctDNA in treatment-naïve individuals are not well established in Indonesia. In recent years, ctDNA as a specific and sensitive blood-based biomarker had been developed to detect the mutation. The study was done to understand the concordance and acceptance levels of ctDNA in detecting the gene mutation in lung adenocarcinoma patients. Methods: This study used cross-sectional approach with purposive sampling design in 100 treatment-naïve NSCLC, adenocarcinoma patients. Samples were obtained from bronchoscopy, and blood, which were examined to detect the mutation in formalin-fixed, paraffin-embedded (FFPE) specimens or plasma samples using QIAampDNA Micro Kit. Mutation was calculated by droplet digital PCR (ddPCR). Results: A hundred subjects with primary tumor tissue samples were compared with the plasma samples and mutation was detected in 20 patients (20.0%), 12 (12.0%) on exon 19, 7 (7.0%) on exon 21 and 1 (1.0%) on both exon 19 and 21. Within the plasma samples, mutation was found in 15 patients (15%) with mutation on exon 19 and 21 in 12 (12.0%) and 3 (3.0%) patients, respectively.  Within the two samples, concordance of EGFR mutation was 83.0% (83/100, P<0.001; correlation index: 0.42). Assuming presence of mutation as the benchmark, the accuracy of mutation presence in plasma DNA was 60.0% (9/15). Kappa test showed a weak agreement between the mutation in tissues and plasma, with a coefficient of 0.414 (95% CI). Conclusion: Tissue biopsy was still considered as the main option to detect EGFR mutation in lung cancer. More research on ctDNA as the standardized tools to detect the mutation are required.